Local and nanoscale methanol mobility in different H-FER catalysts. Issue 5 (2nd February 2022) - Porter, A. J.; Botchway, C. H.; Kwakye-Awuah, B.; Hernandez-Tamargo, C.; Matam, S. K.; McHugh, S. L.; Silverwood, I. P.; de Leeuw, N. H.; O'Malley, A. J.
Abstract : Methanol dynamics in commercial and natural kaolin synthesised FER zeolite catalysts were probed using quasielastic neutron scattering and molecular modelling. Significant differences are observed due to the induced changes in catalyst composition. Abstract : The dynamical behaviour of methanol confined in zeolite H-FER has been studied using quasielastic neutron scattering (QENS) and classical molecular dynamics (MD) simulations to investigate the effects of the Si/Al ratio on methanol dynamics in different Brønsted acidic FER catalysts. QENS probed methanol mobility at 273–333 K in a commercial FER sample (Si/Al = 10) at methanol saturation, and in a FER sample synthesised from naturally sourced Ghanaian kaolin (FER-GHA, Si/Al = 35–48), also at saturation. Limited mobility was observed in both samples and an isotropic rotation model could be fit to the observed methanol motions, with average mobile fractions of ∼20% in the commercial sample and ∼15% in the FER-GHA, with rotational diffusion coefficients measured in the range of 0.82–2.01 × 10 11 s −1 . Complementary molecular dynamics simulations were employed to investigate methanol mobility in H-FER over the same temperature range, at a loading of ∼6 wt% (close to experimental saturation) in both a fully siliceous H-FER system and one with Si/Al = 35 to understand the effect of the presence of Brønsted acid sites on local and nanoscale mobility. The simulations showed that methanol diffusivity was significantly reduced upon introduction of Brønsted acid sites into the system by up to a factor of ∼3 at 300 K, due to strong interactions with these sites, with residence times on the order of 2–3 ps. The MD-calculated translational diffusivities took place over a timescale outside the observable range of the employed QENS spectrometer, varying from 0.34–3.06 × 10 −11 m 2 s −1 . QENS observables were reproduced from the simulations to give the same isotropic rotational motions with rotational diffusion coefficients falling in a similar range to those observed via experiment, ranging from 2.92–6.62 × 10 11 s −1 between 300 and 400 K.